Friction and wear properties of TiN, TiAlN, AlTiN and CrAlN PVD nitride coatings - Aihua, Liu; Jianxin, Deng; Haibing, Cui; Yangyang, Chen; Jun, Zhao (International journal of refractory metals & hard materials, 2012)
Four nitride coatings, TiN, TiAlN, AlTiN and CrAlN were deposited on YG6 (WC+6wt.% Co) cemented carbide by cathodic arc-evaporation technique. The friction and wear properties were investigated and compared using ball-on-disc method at high speed with SiC ball as a counter material. The tests were evaluated by scanning electron microscopy, X-ray diffractometer, energy dispersive X-ray, micro hardness tester and an optical profilometer. The results showed that TiN and TiAlN coatings presented lower friction coefficient and lower wear rate, and that high Al content AlTiN and CrAlN coatings didn't present better anti-wear properties in this test. Oxidation and abrasive wear were the main wear mechanism of TiN coating. In spite of the observation of micro-grooves and partial fractures, TiAlN possessed perfect tribological properties compared with the other coatings. High Al content increased the chemical reactivity and aroused severe adhesive wear of AlTiN coating. CrAlN coating presented better properties of anti-spalling and anti-adhesion, but abundant accumulated debris accelerated wear of the coating under this enclosed wear environment. ► The study was conducted at high speed of 120m/min. ► AlTiN and CrAlN coatings didn't present better anti-wear properties. ► TiAlN possessed the best tribological properties. ► High chemical reactivity aroused severe adhesive wear of the AlTiN coating. ► Accumulated debris accelerated wear of the CrAlN coating.